Using a daily diary approach to understand the psychological experiences of making weight - Sitch, M.; Day, M. (The Sport Psychologist, 2015)
Making weight refers to the process of reducing body weight to compete in weight-categorized sports. The current study explored judo athletes` psychological experiences of making weight. Six international standard judo athletes participated for the length of time they required to make weight. An unstructured diary was used to collect data daily, supported by a follow-up interview. Data were analyzed using a holistic content analysis. Emergent themes included initiating the making weight process, competing demands of dual roles, temptation, impacts of restricted nutrition, and the desire for social support. Athlete stories provided rich descriptions of their experiences, revealing the extent to which difficulties were concealed and the process of making weight was normalized. Their accounts highlight the challenges associated with social support but the value of emotional disclosure. Future research should explore the potential uses of diaries as a form of disclosure.